Strategi Kepemimpinan Kepala Sekolah dalam Membangun Budaya Berprestasi Siswa - Syamsul Arifin; Siti Yusrolana (Idarotuna : Journal of Administrative Science, 2021)
School is an educational institution that has an important role in changing the behavior or abilities of students in the teaching and learning process, as well as instilling a culture of achievement in students. Organizational culture is related to achievement culture, because the advancement of organizational culture is a culture that leads to increased organizational performance, so that the goals set are achieved. The focus of the problem raised is the inculcation of the main values ​​(core values) for students to have a culture of achievement, leadership strategies, their implementation in building a culture of achievement in students at MTs Negeri 1 Lumajang. This research uses descriptive qualitative method, with a case study approach. The results of implementing the madrasa principal's leadership strategy in building a culture of achievement include an increased ethos, a conducive work climate, increased achievement and increased educational productivity.